Supracolloidal Assemblies as Sacrificial Templates for Porous Silk-Based Biomaterials. - Kaplan, David, 1953-; Hardy, John G.; Ghezzi, Chiara E.; Schmidt, Christine E. (Tufts University. Tisch Library., 2016)
Tissues in the body are hierarchically structured composite materials with tissue-specific properties. Urea self-assembles via hydrogen bonding interactions into crystalline supracolloidal assemblies that can be used to impart macroscopic pores to polymer-based tissue scaffolds. In this communication, we explain the solvent interactions governing the solubility of urea and thereby the scope of compatible polymers. We also highlight the role of solvent interactions on the morphology of the resulting supracolloidal crystals. We elucidate the role of polymer-urea interactions on the morphology of the pores in the resulting biomaterials. Finally, we demonstrate that it is possible to use our urea templating methodology to prepare Bombyx mori silk protein-based biomaterials with pores that human dermal fibroblasts respond to by aligning with the long axis of the pores. This methodology has potential for application in a variety of different tissue engineering niches in which cell alignment is observed, including skin, bone, muscle and nerve.